MANAGERIAL ABILITY AS AN EFFORT TO IMPROVE SME PERFORMANCE THROUGH COMPETITIVE ADVANTAGE IN THE PANDEMIC TIME COVID 19 - Ratnawati, Ratnawati; Rokhman, M. Taufiq Noor; Rahayu, Yayuk Ngesti (Jurnal Aplikasi Manajemen, 2021)
The purpose of this study was to investigate competitive advantage as a mediator for the influence of managerial ability on the performance of SMEs in Malang City. The population of this research is the owners of SMEs in Malang, amounting to 113,000 units engaged in food processing, handicraft, and handicraft business units. Sampling in this study using the Slovin formula with a sampling error rate of 5% obtained a total sample of 100 SMEs. The sampling method is through a random procedure (random sampling). Data analysis using Structural Equation Modeling (SEM). The results showed that there is an effect of managerial ability on the performance of SMEs in Malang City and competitive advantage can mediate the effect of managerial ability on the performance of SMEs in Malang City. Future research can analyze the networking capability variables that contribute to the competitive advantage and performance of SMEs.